Hemispherically Organized Sound: Knowing Politics through Music or Music through Politics in the Americas - Daniel Castro Pantoja; Jacob Rekedal (Latin American Research Review, 2017)
This essay reviews the following works: Representing the Good Neighbor: Music, Difference and the Pan American Dream. By Carol A. Hess. New York: Oxford University Press, 2013. Pp. xix + 303. $49.95 cloth. ISBN: 9780199919994. Chilean New Song: The Political Power of Music, 1960s–1973. By J. Patrice McSherry. Philadelphia: Temple University Press, 2015. Pp. xxii + 229. $44.95 paper. ISBN: 9781439911525. Negro Soy Yo: Hip Hop and Raced Citizenship in Neoliberal Cuba. By Marc D. Perry. Durham, NC: Duke University Press, 2016. Pp. ix + 284. $24.95 paper. ISBN: 9780822358855. Remixing Reggaetón: The Cultural Politics of Race in Puerto Rico. By Petra R. Rivera-Rideau. Durham, NC: Duke University Press, 2015. Pp. ix + 224. $23.95 paper. ISBN: 9780822359647. Song and Social Change in Latin America. Edited by Lauren Shaw. Plymouth, UK: Lexington Books, 2013. Pp.vi + 249. $70.00 cloth. ISBN: 9780739179482.